2019
DOI: 10.1007/s12325-019-01142-x
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Treating Early to Moderate Stage Knee Osteoarthritis with Intra-articular Hyaluronic Acid Compared to Conservative Interventions

Abstract: Introduction: Evidence has demonstrated greater benefit of intra-articular hyaluronic acid (IA-HA) within earlier stages of knee osteoarthritis (OA) rather than waiting for patients to have progressed to later stages of disease progression. High molecular weight (HMW) HA has also been shown to be more effective than low molecular weight (LMW) HA products in mild to moderate knee OA, providing an important distinction to make within the class of IA-HA therapies. The purpose of this study is to evaluate the cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…37,40 Furthermore, IAHA was determined to be cost-effective against NSAIDs, corticosteroids, analgesics, 41 and conservative treatment. 43 Nonsteroidal anti-inflammatory drugs are often recommended and prescribed to treat pain in OA; however, if not used appropriately, they can be associated with adverse effects, including gastrointestinal toxicity, cardiovascular toxicity, and risk of acute myocardial infarction and heart failure. 31 This is of particular concern when treating older patients with OA, and these added complications may pose a significant economic burden to the US health care system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…37,40 Furthermore, IAHA was determined to be cost-effective against NSAIDs, corticosteroids, analgesics, 41 and conservative treatment. 43 Nonsteroidal anti-inflammatory drugs are often recommended and prescribed to treat pain in OA; however, if not used appropriately, they can be associated with adverse effects, including gastrointestinal toxicity, cardiovascular toxicity, and risk of acute myocardial infarction and heart failure. 31 This is of particular concern when treating older patients with OA, and these added complications may pose a significant economic burden to the US health care system.…”
Section: Discussionmentioning
confidence: 99%
“…In the worst-case scenario (10% responder rate to IAHA), HMW IAHA was no longer cost-effective in any circumstance. 43 Samuelson et al 44 examined the cost-effectiveness of a series of intra-articular platelet-rich plasma injections (total of 3 injections) compared with IAHA for the treatment of symptomatic knee OA. In the model, the base case assumes an otherwise healthy individual presenting to an orthopedist's office as a new patient for the evaluation and treatment of symptomatic knee OA.…”
Section: Clinical Medicine Insights: Arthritis and Musculoskeletal Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…The study revealed a worldwide prevalence of hip and knee OA in 2017 of around 303.1 million cases and an age‐standardized prevalence estimate of 3754.2 per 100,000 population, with the highest age‐standardized prevalence estimate in the USA (6128.1 cases) and the lowest in Taiwan (2090.3 cases) (Safiri et al, 2020). Acetaminophen, nonsteroidal anti‐inflammatory drugs (NSAIDs), glucosamine, and chondroitin are commonly administered oral treatments for OA (Dorais et al, 2018), while intra‐articular corticosteroid and hyaluronic acid injections or joint replacement surgery are indicated for patients with more severe OA disease (Orchard, 2020; Rosen et al, 2020). Except for joint replacement surgery, all of these clinical treatments focus on reducing chronic inflammation and providing pain relief in OA (Sinusas, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Knee osteoarthritis (KOA) is a local inflammation and chronic strain of the knee joint that causes degeneration of the articular surface cartilage and reactive bone loss of the subchondral bone plate, a range of signs and symptoms in the knee. [ 1 ] The disease is more prevalent in people older than 65 years of age, and there appears to be a trend toward increased incidence in younger age groups. [ 2 , 3 ] The onset of KOA is related to many factors, including gender, [ 4 , 5 ] age, [ 6 ] genetic factors, [ 7 , 8 ] physical factors.…”
Section: Introductionmentioning
confidence: 99%